PENGARUH SENSE MARKETING , THINK MARKETING, RELATE MARKETING TERHADAP KEPUASAN KONSUMEN (Tinjauan Teoritis) - Gita Sugiyarti (Serat Acitya, 2015)
The rapid growth of globalization, the economic crisis and changes in consumer lifestyle proces challenges for marketers in the present. Consumers today have a broad insight in satisfying their needs and desires. The marketers should give weightage in designing an enjoyable consumer experience memorable consumers to concentrate on the pleasure received. The creation of a pleasant and memorable experience to consumers would make them to think about the experience, because it is a sweet spot in their lives. Consumers also make propaganda about the product to their friends and relatives by word of mouth. The purpose of this study was to analyze influence marketing sense, think marketing and marketing relate to consumer satisfaction. The hypothesis proposed there are three, namely: the better the marketing sense, the more meninghkat customer satisfaction; think the better the marketing, the more meninghkat customer satisfaction; the better relate marketing, the more meninghkat customer satisfaction. Keyword : sense marketing , think marketing , relate marketing, customer satisfaction.